Intelligent decision-making system for autonomous robots - Kowalczuk, Zdzisław; Czubenko, Michał (Zielona Góra: Uniwersytet Zielonogórski)
The paper gives an account of research results concerning a project on creating a fully autonomous robotic decisionmaking system, able to interact with its environment and based on a mathematical model of human cognitive-behavioural psychology, with some key elements of personality psychology included. The principal idea of the paper is focused on the concept of needs, with a certain instrumental role of emotions.
Keywords: autonomous robots; artificial intelligence; decision making systems; psychological processes